PENGARUH PRODUK DOMESTIK BRUTO, JUMLAH UANG BEREDAR, INFLASI, CURRENT ACCOUNT, FINANCIAL ACCOUNT, DAN HARGA MINYAK DUNIA TERHADAP KURS RUPIAH PER DOLAR AMERIKA SERIKAT TAHUN 2002-2012 - Hakim, Nurul; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2013)
Exchange rate is an important issue to provide foreign Investment and foreign funding. Butsince free-floating axchange rate system has been applied in Indonesia, the movement of Rupiah against the US Dollar is hard to predicted. This condition brings many argumentations about the reasons behind the exchange rate instability whether it is caused by economic factors or by non- economic factors. By recognizing the causes, it will be easier for the fund seeker and investor of Indonesia to formulate the solution.This study aimed to analyze the influence of GDP, Money Supply, inflation, current account, financial account, and world oil prices to the exchange rate of Rupiah per U.S. Dollar. This study was made as there are differences between the results of research with each other and so can be used to predict fluctuations in the exchange rate of Rupiah per U.S. dollar.This study uses multiple linear regression statistic to test the hypothesis. The variable used in this study is Rupiah per U.S. Dollar, GDP, Money Supply, inflation, current account, financialaccount, and world oil prices. Type of data used in the form of time series data that restricted tothe data of each variable quarterly starting from the period Q1 2002 to Q4 2012 period.The results showed that the Money Supply and financial account has significant positive effect on Rupiah per U.S. Dollar exchange rate. While world oil prices has significant negativeeffect on the exchange rate of Rupiah per U.S. Dollar. Meanwhile, GDP, inflation, and current account does not affect the exchange rate of Rupiah per U.S. Dollar. In addition it was found thatthe value of adjusted R square is 64,9%. This means that 64.9% of the movement of Rupiah perU.S. Dollar exchange rate can be predicted from the six variables, while at 35,1% is explained by other variables outside the model.